Strategy improving students' understanding of multiplication concepts through abacus props abacus 100 beads class 2 sd negeri 0119 banjar raja - Hasibuan, Muhammad Asyhari; Harahap, Nurhalimah; Mutiah, Era (Trigin Institute, 2024)
Muhammad Asyhari Hasibuan.